Kontribusi konsultan pajak meningkatkan kepatuhan wajib pajak orang pribadi - Arifudin Arifudin; Wulan Dri Puspita (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This research seeks to determine and analyze the contribution of tax consultants to enhance the compliance levels of individual taxpayers, with a focus on those registered at the Dwi Achmad Tax Consultant Office. The study utilizes a qualitative methodology with a descriptive approach, gathering data through interviews with tax consultants. The findings reveal that individual taxpayers continue to face several challenges in meeting their tax obligations. These challenges include limited understanding of tax regulations, inefficient use of tax applications, confusion about regulatory changes, poor organization of transaction’s documents, and insufficient financial record-keeping. Such conditions elevate the risk of errors in tax reporting and payment. Therefore, the Dwi Achmad Tax Consultant plays a crucial role in providing tax education and guidance to individual taxpayers, offering consultation and assistance in resolving tax-related issues, and reducing their concerns and fears regarding tax sanctions. Tax consultants also contribute by encouraging greater tax compliance and helping optimize tax calculations and payments in accordance with applicable laws and regulations.